The Fanon reader : Frantz Fanon - Fanon, Frantz (Pluto, 2006)
The Fanon reader features extracts from each of Fanon's major works, including Black skin, white masks, Studies in a dying colonialism, Toward the African revolution, and The wretched of the Earth. Haddour contextualises Fanon, the man and his work, and provides a comprehensive summary of critical perspectives on his writings.